2006
DOI: 10.1192/pb.30.4.142
|View full text |Cite
|
Sign up to set email alerts
|

Examining the concept of patient satisfaction in patients with a diagnosis of schizophrenia: a qualitative study

Abstract: Examining the concept of patient satisfaction in patients with a diagnosis of schizophrenia: a qualitative study AIMS AND METHODTen people with a diagnosis of schizophrenia were interviewed. The interviews were analysed qualitatively with the aim of examining the concept of patient satisfaction in the context of a recent in-patient admission. RESULTSThe analysis identified two themes that influenced the expression of patient satisfaction: external factors and internal factors. The theme of external factors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…Those that felt they were prematurely discharged were more likely compared to others to report dissatisfaction with help received from physicians, and were less likely to feel that staff had time for them (Gjerden, 1997). Qualitative research (Duggins and Shaw, 2006) found that higher satisfaction was related to low initial expectations of the service. The remaining study found that satisfaction was significantly lower in those who felt that they did not need to be hospitalised (Barker et al, 1996).…”
Section: Perceptions Of Need For Hospitalisation and Illnessmentioning
confidence: 99%
See 4 more Smart Citations
“…Those that felt they were prematurely discharged were more likely compared to others to report dissatisfaction with help received from physicians, and were less likely to feel that staff had time for them (Gjerden, 1997). Qualitative research (Duggins and Shaw, 2006) found that higher satisfaction was related to low initial expectations of the service. The remaining study found that satisfaction was significantly lower in those who felt that they did not need to be hospitalised (Barker et al, 1996).…”
Section: Perceptions Of Need For Hospitalisation and Illnessmentioning
confidence: 99%
“…Studies suggested that satisfaction was lower in participants who felt that they were not in need of hospital treatment (Barker et al, 1996), that they had been discharged too early (Gjerden, 1997), or had low initial expectations of the service (Duggins and Shaw, 2006). Those that felt they were prematurely discharged were more likely compared to others to report dissatisfaction with help received from physicians, and were less likely to feel that staff had time for them (Gjerden, 1997).…”
Section: Perceptions Of Need For Hospitalisation and Illnessmentioning
confidence: 99%
See 3 more Smart Citations